Meat Quality Comparison in Bali, Wagyu, and Their Cross-Breed Cattle Using Ultrasound Imaging - Setyani, Ni Made Paramita; Priyanto, Rudy; Ulum, Mokhamad Fakhrul; Sutikno, Sutikno; Jakaria, Jakaria (Jurnal Agripet, 2024)
This study aimed to compare the meat quality of different beef cattle breeds using ultrasound imaging. A total of 28 cattle, aged 1-2.5 years, from three breeds were analyzed: Wagyu (n=7), Bali (n=10), and WagyuBali cross-breeds (n=11). Meat quality traits, including longissimus dorsi thickness (LDT), backfat thickness (BFT), intramuscular fat (IMF), and marbling score (MS), were assessed using ultrasound imaging. The association between breed and meat quality was analyzed using a completely randomized design (CRD) followed by Tukey's test. Additionally, principal component analysis (PCA) was employed to identify clusters of meat quality potential among the different breeds. The results indicated that WagyuBali cross-breeds exhibited the highest LDT (46.3804.770 mm), though the difference was not statistically significant (P0.05) compared to either Bali or Wagyu cattle. However, significant differences (P0.05) were observed between Bali and Wagyu cattle. For BFT, MS, and IMF, Wagyu cattle outperformed both Bali cattle and WagyuBali cross-breeds, with values of 5.4900.806 mm, 6.0100.998, and 49.058.140%, respectively. The PCA revealed two primary clusters: the first cluster, comprising Wagyu cattle, accounted for 75.6% of the diversity and was characterized by BFT, IMF, and MS as key variables. The second cluster included Bali cattle and WagyuBali cross-breeds, representing 21.5% of the diversity, without any specific meat quality variable as a defining marker. Ultrasound imaging effectively estimated meat quality in Bali cattle and their cross-breeds, demonstrating its potential as a tool for meat quality assessment across different breeds.